2023
DOI: 10.1021/acs.jafc.2c07139
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Layer-By-Layer Coating as a Procedure to Enhance Lactobacillus plantarum Survival during In Vitro Digestion, Storage, and Fermentation

Abstract: Probiotics are sensitive to phenolic antibacterial components and the extremely acidic environment of blueberry juices. Layer-by-layer (LbL) coating using whey protein isolate fibrils (WPIFs) and sodium alginate (ALG), carboxymethyl cellulose (CMC), or xanthan gum (XG) was developed to improve the survival rate of Lactobacillus plantarum 90 (LP90) in simulated digestion, storage, and fermented blueberry juices. The LbL-coated LP90 remained at 6.65 log CFU/mL after 48 h of fermentation. Scanning electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The data showed that the count of free cells reduced from 8.67 log CFU/mL to 1.27 log CFU/mL with a viability of 14.68% after 60 days of storage at 4°C. However, the survival rate of encapsulated bacteria was 60% (Li et al., 2023 ). It differs from the current research results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data showed that the count of free cells reduced from 8.67 log CFU/mL to 1.27 log CFU/mL with a viability of 14.68% after 60 days of storage at 4°C. However, the survival rate of encapsulated bacteria was 60% (Li et al., 2023 ). It differs from the current research results.…”
Section: Resultsmentioning
confidence: 99%
“…However, the reduction of MLC was 2.19 log CFU/mL, and the survival rate was 77.85% during storage. Similarly, Li et al (2023) used protein-isolated fibrils, sodium alginate, carboxymethylcellulose, and xanthan gum to protect Lactobacillus plantarum. The data showed that the count of free cells reduced from 8.67 log CFU/mL to 1.27 log CFU/mL with a viability of 14.68% after 60 days of storage at 4°C.…”
Section: Survival Of Mlc and Flc In Avjd During The Storage Timementioning
confidence: 99%
“…235 These nanofilms created a synthetic cellular environment on cell membranes, facilitating the regulation of cell viability, morphology, and proliferation, especially in osteogenesis or bone formation. 236 Moving beyond protein-based coatings on cellular surfaces, Li and colleagues 237 developed an effective encapsulation strategy for probiotics using the LbL assembly method, leveraging electrostatic interactions and hydrogen bonds among fibrils from various sources. Encapsulated probiotics exhibited significantly improved survival rates during simulated gastrointestinal digestion and storage.…”
Section: Lbl Assemblymentioning
confidence: 99%
“…Moving beyond protein-based coatings on cellular surfaces, Li and colleagues 237 developed an effective encapsulation strategy for probiotics using the LbL assembly method, leveraging electrostatic interactions and hydrogen bonds among fibrils from various sources. Encapsulated probiotics exhibited significantly improved survival rates during simulated gastrointestinal digestion and storage.…”
Section: Artificial Strategies Of Protein-based Bioactive Coatings In...mentioning
confidence: 99%
“…Microencapsulation of probiotics is an effective and feasible method to enhance their stability and cell survival. In addition to improving the survival rate of probiotics during gastrointestinal digestion, microencapsulation technology can also promote the stability of probiotics by preventing adverse reactions with external factors and ensuring controlled and targeted release in the gastrointestinal tract [2].…”
Section: Introductionmentioning
confidence: 99%